Report of Health Week Committee
1924-02-25 1924 1920s 4 pages HEALTH WEEK COMMITTEE OF THE ROYAL SANITARY INSTITUTE. [Image] Patrons: HIS MAJESTY THE KING. HER MAJESTY THE QUEEN. Report of Health Week Committee, February 25th, 1924. It would appear that the week was observed with even more enthusiasm than usual. Health Week celebrations were arranged in over 90 centres and it is interesting to note that these are spread throughout Great Britain, and also throughout the Empire, there being four in India — Ahmedabad, Bijapur, Madras and Karachi; five in Africa — Accra (Gold Coast), Capetown, Mossel Bay, Port Elizabeth and Pretoria; five in Australia — Brisbane (Queensland), South Brisbane (Queensland), Caulfield (Victoria), Ithaca (Queensland), and Melbourne (N.S.W.); one in Canada — Edmonton (Alberta); two in the West Indies — Kingston (Jamaica) and Portland (Jamaica). The comprehensive nature of many of the programmes is illustrated by the West Riding, Yorks, where some 150 medical men co-operated with the Public Health and Insurance Committees in giving addresses to school children and others throughout the Riding. In all addresses were given. Elementary Schools. Secondary Schools. Total. Medical Practitioners 242 2 244 Head Teachers 540 48 588 782 50 832 214,000 of each of three leaflets were distributed to the Scholars in the Schools; 1,923 letters were addressed to Ministers of religion, many of whom made Health the subject of their sermons; and lessons were given in the Sunday 292/842/1/10